PECULIARITIES OF ADAPTATION PROCESSES OF THE MEDIEVAL POPULATION OF THE PERM CIS-URALS: ANTHROPOECOLOGICAL APPROACH - Bryukhova, N.G. (Perm Federal Research Centre Journal, 2017)
A description of adaptive peculiarities of the ancient population of the Perm Cis-Urals is presented on the basis of a reconstruction of the human nutrition system and morpho-physiological traits of medieval inhabitants of this territory. The study is based on the analysis of anthropological materials with the use of bio-archaeological, craniometric methods and osteometry involving the results of the isotopic analysis. Based on the research, a conclusion is made, that over a period of a thousand years (the 4th - the 15th centuries), the medieval population of the territory under consideration had similar adaptive traits, typical of representatives of forest continental groups and was well adapted to life in taiga forest zone.